Germansk dyrestil (Salins stil I-III): Et historisk perspektiv - Nielsen, Karen Høilund; Kristoffersen, Siv (Hikuin, 2002)
Germanic Animal Art (Salin’s Styles I-III) A historical perspective By Karen Høilund Nielsen & Siv Kristoffersen The study of animal art has been a strong tradition within archaeological research in northern Europe and Scandinavia. The history of this field of research provides a perspective that helps one to understand the development of archaeology as a whole. Many scholars have contributed to the study of Germanic animal art, and an attempt is made to highlight the most important of these. This stands alongside an attempt to present the study of animal art in its entirety, in order to reveal the various research traditions. This is accompanied by a focus upon the individual scholars and their involvement in various debates, both of a methodological or theoretical character, and in respect of interpretation. The history of the subject is divided into five principal sections. Under the first, Animal art becomes a science, the slender beginnings under C.J. Thomsen and Oscar Montelius are discussed, as well as the man who truly put the issue on the map, Sophus Müller. His thesis of 1880 considered most of the questions that have since remained live. The study of animal art became a scientific academic discipline, and attention was focussed upon understanding of the societies that produced these styles. It was Montelius, however, who set the standard for the next generation, which consisted of Typologists and Art Historians such as Bernhard Salin, Nils Åberg, Sune Lindqvist and Haakon Shetelig. In their time, animal art became the central focus of research concerning the late Iron Age and early Middle Ages. They laid a foundation that is very much the one we work upon today. A large corpus of material was presented, covering most of the area in which animal art is found. The analysis of the style was divided between two different schools, one of which worked with individual style-elements and the other with whole compositions. The division into Styles I-III stood firm, and a sub-division of Style II was being developed. The origins of the styles remained a matter of discussion, however, even though the general view attributed Styles I and II to a Continental source. New finds such as those from the Vendel burials and the Oseberg ship grave affected the discussions. Under The Second Generation – Regionalism, scholarship became more inward looking, with an emphasis on the publication of new excavations and attempts to look at the meaning of the finds in their local areas. In one way this ushered in a sort of regionalism. Finds such as Snartemo and Valsgärde were important in this phase. The leading figures were Wilhelm Holmqvist, T. D. Kendrick, E. T. Leeds, Eva Nissen Meyer, Bjørn Hougen, Greta Arwidsson, Pär Olsén and J.-E. Forssander. Holmqvist was one of the few who continued to work with styles generally on a European scale. Regional studies were otherwise undertaken for Anglo-Saxon England, Norway, and parts of Uppland. While Holmqvist, as also Nissen Meyer and Hougen, kept faith with Salin’s stylistic groupings, the analyses of the finds from England and the Valsgärde burials saw some breaking away from this line. The social aspect was emphasized by Nissen Meyer, Holmqvist and the Uppsala school. This also involved increasing attention to the religions, social and political contexts. There was growing focus on Scandinavia as the most informative area in respect of animal art, as Holmqvist argued that Style II had been created there, while Leeds came to the conclusion that Anglo-Saxon Style I must have come to England from Scandinavia. The study of animal art and archaeology itself changed character with the Second World War. The scholars who then led the field had one thing in common – consciously or not, an anxiety over the potential misuse of their ideas. This led to positivism and logical positivism together with New Archaeology, and insistent demands that only that which could be measured, weighed, or directly observed could used as evidence became central. Objective scholarship was the target. Under the heading The Lost Innocence and Puritanism belong the scholars Bertil Almgren, Mats P. Malmer, Mogens Ørsnes, Egil Bakka, Günter Haseloff and Helmut Roth. The extensive excavations at Helgö brought production into the range of topics and the animal art of eastern Scandinavia was presented in Aarni Erä-Esko’s dissertation. In Germany the contents of the animal motifs were discussed in relation to the iconographical tradition by scholars such as Herbert Kühn, Hayo Vierck and Helmut Roth. The relationship between Germanic animal art and Late Roman arts was the subject of works by Horst Wolfgang Böhme and Sonia Chadwick Hawkes. In the section Symbolism and the New Culture Historians the »young Turks« join in, style-specialists who have made their mark from about 1980 onwards. These have attempted to a greater or lesser degree to bring out new aspects of the study of style and to place it within a different framework. This has gone hand in hand with increasing interest in theoretical archaeology and greater attention to symbols and the role of material culture in the mental and social spheres. Such work provides a basis for a quite different conception of the place of animal art in Iron-age society. In England it has been David Leigh and George Speake who have built further upon the classical traditions of style history. In Scandinavia we see individuals who broke radically away from the existing situation such as Arne B. Johansen and Lennart Karlsson. Throughout the period in which the animal styles have been discussed, attempts have been made to place the decorative art in the context of the development of Iron-age society, and one scholar who has particularly sought to integrate the style into the political and social development of the age and to link this with religion and cosmology is Lotte Hedeager. Complementing the theoretical impulses of this phase, Karl Hauck has been a highly influential figure. Hauck works in the tradition of German art history with iconographical analysis and investigating the iconographical context. Motif-interpretation of this kind can be found in the work of several scholars, such as Bente Magnus. For a long time scholars disputed over the origins of the styles, especially Style II – now it has become a basic premiss to see the animal styles as something essentially Nordic. This has opened the way for the study of style to take on a significance beyond typology or chronology, an opportunity which has slowly, hesitantly, but increasingly been taken up. This has led to the situation in which Germanic animal art is seen as a gateway to lost myths, beliefs, cosmology, political divisions, and more: quite simply the gateway to the immaterial world that archaeologists have long regarded as essentially untouchable. In the work of the most recent generation of researchers in this field, the animal art itself, modern social theories, and the progressive German tradition of art history have come together. The latter has been lurking in the wings all the time, but it has taken three-quarters of a century for archaeologists to embrace it.